Optimization of Sample Preparation and Analytical Performance Evaluation for a Model Polar Compound in Hydroxypropyl Methycelulose-Based Controlled-Release Tablets - Bozhinovska, Marijana; Achkoska, Tina; Atanasova, Ana; Antovska, Packa; Gigopulu, Olga; Poceva Panovska, Ana (Archives of Pharmacy, 2026)
Controlled-release (CR) tablets based on hydroxypropyl methylcellulose (HPMC) provide numerous therapeutic advantages, but pose significant analytical challenges during the assay of polar active substances due to the polymer’s high swelling capacity and gel-forming behaviour. This study aims to develop and evaluate a robust two-step sample preparation procedure that ensures complete extraction and accurate quantitation of a model polar basic compound incorporated into an HPMC matrix. Various diluents and agitation techniques were systematically compared to identify conditions enabling full recovery of the analyte. The optimized workflow involved initial extraction with acetonitrile for 15 minutes under ultrasonic agitation, followed by hydration with water for 45 minutes under magnetic stirring. The samples were analysed with High-performance liquid chromatography (HPLC) analysis, using ion-pair reversed-phase conditions. Acetonitrile effectively disrupted the HPMC network, preventing gel entrapment and yielding quantitative recovery (100 ± 0.5%) with excellent reproducibility (RSD < 1%). The analytical method demonstrated linearity (R² = 0.9997), accuracy (99.6 %), precision (RSD ≤ 0.5%), robustness, and solution stability consistent with ICH Q2 (R2) principles. The proposed two-step acetonitrile-water extraction provides a reliable, transferable strategy for the assay of polar drugs in HPMC-based controlled-release formulations and can serve as a methodological framework for future compound-specific validation.